Adaptive evolution of distinct prey-specific toxin genes in rear-fanged snake venom. Issue 1884 (1st August 2018) - Modahl, Cassandra M.; Mrinalini,; Frietze, Seth; Mackessy, Stephen P.
Abstract : Venom proteins evolve rapidly, and as a trophic adaptation are excellent models for predator–prey evolutionary studies. The key to a deeper understanding of venom evolution is an integrated approach, combining prey assays with analysis of venom gene expression and venom phenotype. Here, we use such an approach to study venom evolution in the Amazon puffing snake, Spilotes sulphureus, a generalist feeder. We identify two novel three-finger toxins: sulditoxin and sulmotoxin 1. These new toxins are not only two of the most abundant venom proteins, but are also functionally intriguing, displaying distinct prey-specific toxicities. Sulditoxin is highly toxic towards lizard prey, but is non-toxic towards mammalian prey, even at greater than 22-fold higher dosage. By contrast, sulmotoxin 1 exhibits the reverse trend. Furthermore, evolutionary analysis and structural modelling show highest sequence variability in the central loop of these proteins, probably driving taxon-specific toxicity. This is, to our knowledge, the first case in which a bimodal and contrasting pattern of toxicity has been shown for proteins in the venom of a single snake in relation to diet. Our study is an example of how toxin gene neofunctionalization can result in a venom system dominated by one protein superfamily and still exhibit flexibility in prey capture efficacy.